2020
DOI: 10.32598/ijmtfm.v10i2.28112
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Pattern and Frequency of Road Traffic Injuries in Car Occupants in the Eastern Part of Iran

Abstract: Background: Since Iran has one of the highest mortality rates of car accidents in the world, the study of the pattern and reasons of trauma in car occupants can provide useful information to determine the underlying causes of injuries and deaths in traffic accidents. Accordingly, this study was conducted to determine the pattern, frequency, and causes of traumatic injuries caused by traffic accidents in car occupants.Methods: This cross-sectional study was conducted during the first 6 months of 2017 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…There was a significant positive relationship between the constructs of the TPB with behavioral intention and traffic behaviors. The results of the present study are in line with the results of a study performed by Soroosh et al (8), in which of 300 individuals, 58.3% declared that they always fasten their seat belts. The current study's results revealed a positive and significant relationship between safety traffic behaviors and prosafety attitudes.…”
Section: Resultssupporting
confidence: 93%
“…There was a significant positive relationship between the constructs of the TPB with behavioral intention and traffic behaviors. The results of the present study are in line with the results of a study performed by Soroosh et al (8), in which of 300 individuals, 58.3% declared that they always fasten their seat belts. The current study's results revealed a positive and significant relationship between safety traffic behaviors and prosafety attitudes.…”
Section: Resultssupporting
confidence: 93%